Abnormal cervical cytology is associated with preterm delivery: A population based study. (13th February 2019) - Jar‐Allah, Tagrid; Kärrberg, Cecilia; Wiik, Johanna; Sengpiel, Verena; Strander, Björn; Holmberg, Erik; Strandell, Annika
Abstract: Introduction: Increasing evidence suggests that cervical intraepithelial neoplasia, with or without subsequent treatment, is associated with preterm delivery. We aimed to explore the association between abnormal cervical cytology of different severity and the subsequent obstetric outcomes such as preterm delivery. Material and methods: The historical register‐based cohort study comprised 19 822 women in the Western Region of Sweden who had at least one abnormal cervical cytology from 1978 to 2012 before the age of 45 and a subsequent singleton delivery. The reference group comprised 39 644 women with normal cervical cytology and a subsequent singleton delivery, matched by age and parity. Data were retrieved from the Swedish National Cervical Screening Registry, linked to the Swedish Medical Birth Register and Statistic Sweden. The study outcomes were spontaneous preterm delivery before 37 and 34 weeks, low birthweight (≤2500 g), small‐for‐gestational‐age, preterm premature rupture of membranes and neonatal mortality. Multivariable log binominal regression analyses were applied. Results: Preterm delivery before 37 weeks was more common among women with abnormal cervical cytology compared with reference group: 6% vs 4.5%; adjusted relative risk 1.30 (95% confidence interval 1.21‐1.39). High vs low‐grade abnormal cervical cytology implied a higher risk: 7% vs 5.8% ( P < 0.001). Early preterm delivery before 34 weeks, preterm premature rupture of membranes and low birthweight, but not small‐for‐gestational‐age and neonatal mortality, were significantly more common in women with abnormal cervical cytology compared with the reference group. Conclusions: Abnormal cervical cytology may imply an increased risk of preterm delivery. Further studies are needed to investigate whether that risk is related to treatment.